THE EFFECT OF STUDENT PRESENTATION ON THE ELEVENTH GRADE STUDENTâ€™S SPEAKING SKILL AT SMA NEGERI 24 KABUPATEN TANGERANG - Retno Puji Astuti; Abdul - Rohim (Globish: An English-Indonesian Journal for English, Education, and Culture, 2018)
AbstractREFERENCESBenyamin, H. (2012). Advanced Learning English 2 for Grade XI Senior High School. Bandung: Grafindo Media Pratama.Biadoll123. (2014). â€œEffective Presentation Skillâ€ Journal Education-Business: 1-30. http://www.slideshare.net/biadoll123/effective-presentation-skills-29762969 (Accessed on January, 7th, 2014)Brown, D. H. (2003). Language Assessment Principles and Classroom Practices. California: Longman.---------------. (2004). Language Assessment Principles and Classroom Practices. California: Longman.Chomsky, N. (2006). Language and Mind. Third Edition. New York: Cambridge University PressColman, M, A. (1996). â€œTeaching presentation skills to undergraduates: studentsâ€™ evaluations of a workshop course.â€ Journal Education: 75-82. https://www2.le.ac.uk/departments/npb/people/amc/articles-pdfs/teacpres.pdf (Accessed on January, 2nd, 2016)Dewi, P,R. (on Friday, October, 2014) Presentasi. Accessed from http://dhytadwias.blogspot.co.id/2014/09/presentasi.htmlFakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Tangerang. (2015). Pedoman Penulisan Skripsi. Tangerang: UMT Pres.Fakultas Ekonomi Universitas Negeri Yogyakarta. (2014). Tantangan dan Keuntungan AFTA 2015 untuk Indonesia. Yogyakarta: WordPress.com.Gibson, M. (2013). Types of Presentations. Arkansas: Henderson State University. https://www.accuconference.com/blog/types-of-presentations/ (Accessed on October, 25th, 2013)Griffiths, C. (2008). Lesson from Good Language Learners. New York: Cambridge University Press.Haber, G. (2008).â€( Benefits of Student Verbal Presentations to the Class.â€ Journal English Teacher Network: 1. http://www.etni.org.il/etnirag/issue9/gilda_haber.htm (Accessed on December, 12th, 2015)Harmer, J. (2007). The Practice of English Language Teaching. Third Edition. English: Cambridge.Hughes, R. (2002). â€œThe Effect of Intensive Communication Activities to Improve Novice Learnersâ€™ Oral Interaction Skill.â€ Journal of English: 135. http://www.paaljapan.org/resources/proceedings/PAAL10/pdfs/negishi.pdf (accessed on December, 1st, 2015)Itâ€™s Time to Go to School! Short Example of Spoof Text. (on June 2013) Accessed from http://freeenglishcourse.info/its-time-to-go-to-school-short-example-of-spoof-text/Louma, S. (2004). Assessing Speaking. Cambridge: Cambridge University Press.Mandel, S. (2000). Effective Presentation Skill. Boston: United States of America.Mutiara, M, N, S. (on January, 24th, 2016). Personal Interview.Nita, W, A. (2015). Effect of Presentation on the Eleventh Grade Studentâ€™s Speaking Skill at SMA 14 Kabupaten Tangerang. Program Sarjana Fakultas Keguruan dan Ilmu Pendidikan Bahasa Inggris. Tangerang: Universitas Muhammadiyah Tangerang.Pollard, L. (2008). Lucy Pollardâ€™s Guide to Teaching English. London: University of London.Prabowo, D, A. (on January, 3th, 2013). Example of Spoof Text, Definition, Generic Structure, and Purpose. Accessed from http://di-copy.blogspot.co.id/p/about-us.htmlRiadi, E. (2014). Metode Statistika Parametrik & Nonparametrik. Tangerang: Pusaka Mandiri.Sriwismajayanti. (on July, 28th, 2010) Definition of Spoof Text. Accessed from https://sriwismajayanti.wordpress.comSugiono. (2013). Metode Penelitian Kuantitatif dan Kualitatif dan R&D. Bandung: Alfabeta.------------------ (2003). Metode Penelitian Kuantitatif dan Kualitatif dilengkapi dengan R&D. Bandung: Alfabeta.Tornbury, S. (2005). How to Teach Speaking. Vermont: LongmanWallwork, A. (2010). English for Presentations at International Conferences. New York: Spinger.Yunita, N. (2014). Improving the Eleventh Grade of Administration Studentâ€™s Speaking Skill through Role Play Strategy at SMK Harapan JayaÂ Cengkareng. Program Sarjana Fakultas Keguruan dan Ilmu Pendidikan Bahasa Inggris. Tangerang: Universitas Muhammadiyah Tangerang